The effect of arm muscle power and confidence on the ability of the volley smash ball - Tjung Haw Sin; Nopianto Nopianto; Adnan Fardi (Global Econedu, 2020)
The problem in this study originated from the low ability of the Smash of the men’s volleyball players in the Palembang City MBVC Club, such as Smash not being on target, leaving the field and blocked. The low ability of Smash is influenced by several exogenous factors, including Arm muscle power and Confidence in Smash ability, and. This research is quantitative with a path analysis approach. The population in this study were all male volleyball players from the Palembang City MBVC Club, amounting to 20 people. Sampling uses a saturated sampling technique, so it samples all populations. The arm muscle instrument uses One Hand Medicine Ball Put, uses a Likert scale model questionnaire and Smash ability with the Smash test. The results showed that, (1) there was a direct effect of arm muscle power on the ability of Shash, with py1 = 0.386 or 14.90% (2) there was a direct trust effect on Shash ability,, with py2 = 0.382 or 14.59% (3) There is an indirect effect of arm muscle power on the ability of Smash through self confidence, with py21 = 0.1574 or 15.74%.